STATE OF THE ART ‘ENTREPRENEUR+SUFIKS’: SEBUAH STUDI PEMETAAN SISTEMATIS (State of the Art of ‘Entrepreneur+Suffixes’: A Systematic Mapping Study) - Margo Purnomo (SAWERIGADING, 2021)
Along with the high attention and publications on entrepreneurship in various fields, it is often found that consumers/producers of scientific/non-scientific publications in the field of entrepreneurship have difficulty to understand of various word formations that come from the basic word: ‘entrepreneur’. One of the problems that arise is understanding the various formations of the word 'entrepreneur+suffix' in English. With this into account, this article aims to explore the diversity of word formations: 'entrepreneur+suffix’ in scientific publications. For this reason, a systematic mapping study (SMS) on two electronic databases was carried out. The mapping results identified 91 formations of the word 'entrepreneur+suffix' which have been recorded historically since 1859. The map of various word formations 'entrepreneur+suffix' recommends that consumers/producers of scientific/non-scientific entrapreneurship publications must be extra careful in translating and understanding them AbstrakSeiring dengan tingginya perhatian dan publikasi pada entrepreneurship di berbagai bidang, sering ditemui konsumen/produsen publikasi ilmiah/non ilmiah di bidang entrepreneurship mengalami kesulitan dalam memahami aneka bentukan kata yang berasal dari kata dasar: ‘entrepreneur’. Salah satu permasalahan yang muncul adalah memahami aneka bentukan kata ‘entrepreneur+sufiks’ dalam Bahasa Inggris. Mempertimbangkan hal tersebut, artikel ini bertujuan untuk mengeksplorasi keanekaragaman bentukan kata: ‘entrepreneur+sufiks pada publikasi ilmiah. Untuk itu, studi pemetaan sistematis (systematic mapping study/SMS) pada dua basis data elektronik dilakukan. Hasil pemetaan teridentifikasi 91 bentukan kata ‘entrepreneur+sufiks’ yang secara historis terdata sejak tahun 1859. Peta aneka bentukan kata ‘entrepreneur+sufiks’ merekomendasikan agar para konsumen/produsen publikasi entrapreneurship ilmiah/non ilmiah harus ekstra hati-hati dalam menerjemahkan dan memahaminya.